Pengaruh Intensitas Penggunaan Aplikasi Tiktok terhadap Prokrastinasi Akademik Peserta Didik Kelas VIII SMP Negeri 1 Sungai Raya - Justiadila, Shabrina Rizki; Asrori, Muhammad; Wicaksono, Luhur (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
Education to be major the important aspect towards humans because it can create quality humans in people's lives. Processing education, students are required could be able to face and undergo the provisions that exist in academic life. In today's digital era, technology and social media are developing precipitately, made it easue towards user to access social media freely. Become popularity one of kinds of media social is TikTok. It is known that students are very fond of using TikTok by reason of it, this platform could be able entertain user whenever they were boring. Excessive use of TikTok will have an impact on students' academic performance. Many students cannot undergo the provisions that exist in academic life, one of which is doing assignments. Learners delay doing assignments and cause a mismatch between educational goals and existing realities. The purposelly this reseach was to established the grade the intensity of TikTok uses and the level of academic procrastination of eight grade students in SMP Negeri 1 Sungai Raya, as well as the impact towards intensity of TikTok using towards academic procrastination of students in SMP Negeri 1 Sungai Raya. The yields of this reseach has impact towards intensity of using the TikTok application on the academic procrastination of students in SMP Negeri 1 Sungai Raya with an effect of 22.9%.